Flexibility matters: Impact assessment of small and medium enterprises flexibility on the German energy transition - Anas Abuzayed; Mario Liebensteiner; Niklas Hartmann (Energy Conversion and Management: X)
This study analyzes the transition of the German electricity system towards climate neutrality by 2045, considering the demand-flexibility from small and medium enterprises (SME). The research uncovers the potential of flexibility from often-overlooked industrial SME sector, challenging their historical neglect in energy models and national strategies. Despite representing a small fraction of peak load, SME flexibility contributes to a significant reduction in carbon emissions and transition costs, as well as a decreased reliance on other flexibility measures. However, careful design and incentivization strategies are vital to reap the full benefits of SME flexibility. Challenges in achieving a secure electricity supply during extreme weather conditions in a 100 % renewable system are identified, along with how SME flexibility helps to achieve climate neutrality. By 2045, wind power becomes vital for supply security and is operated as a dispatchable ramping-up technology. Storage flexibility becomes essential. The transition incurs substantial costs but is economically advantageous in the long run. Overcapacities from renewables allow for a higher degree of electrification, stronger sector coupling, and suggest the possibility of a local hydrogen production. Although our study examines the flexibility of German SME, demand-responsive technologies exist worldwide, however with different shares and potentials. The study provides valuable insights into how SME demand response can contribute to achieving a sustainable energy system.